A Synchronic Sociolinguistic Analysis of Personal Names Among Ewes - Abdul, R.E. (University of Ghana, 2014)
The study is a synchronic sociolinguistic analysis of personal names among Ewe people in Ghana. It treats as its background Egblewogbe’s (1977) thesis in which he describes vividly the various types of Ewe names, their linguistic structure and their semantics. In this study a variationist sociolinguistic analysis is made to determine age, gender and regional and variations in personal names being given among the Ewe people. Four types of data were collected: registers from three Senior High schools, questionnaires, interviews, and personal observation. The study shows that the Ewe naming system has undergone some transformations due to language and religious contacts. It is shown among other things that there is a shift from traditional Ewe names to Ewe Christian religious names among Ewe people and the factors responsible for this shift are highlighted. The analysis also shows that Ewe personal names are marked morphologically and conventionally for gender. For the geographical variation, it is shown that some Ewe personal names vary depending on the location of the name bearer. The age-based variations also show that the older folks bear more Ewe names than the younger folks. On the dynamics of the use of names, the study shows that Ewes are addressed differently in different social domains depending on the participants involved in the interaction and the number of names they bear. Finally, the study shows that there is a discrepancy between the respondents’ preference for their personal names and their attitudes towards the use of their Ewe names.
Thesis (MPHil) -University of Ghana, 2014